A novel and easy‐to‐implement modulation scheme for reducing modulation complexity in modular multilevel converter - Zichen Wang; Zhijie Liu; Ke‐Jun Li; Jinxin Dou; Zhonglin Guo; Xiaoxue Ge (IET Power Electronics)
Abstract Modulation strategy plays a key role in the operation of modular multilevel converters (MMC). Although many studies have been carried out on its optimization in MMC, the limitations of hardware implementation are seldom considered. This paper presents a novel and easy‐to‐implement modulation strategy that simplifies both hardware design and application. From the analysis in this paper, the widely‐used modulation methods have the problems of pulse width modulation (PWM) signal feedback and complex carrier configuration in hardware implementation. By setting up a flexible insertion and removal submodule and proposing a capacitor voltage balance algorithm based on duty ratio allocation, the proposed modulation method can allow for the separate design of the Algorithm Unit and the PWM Unit in the hardware, which solves the problem of PWM feedback and reduces the hardware requirement of the trigger system. Moreover, the proposed method can broaden the selection range of processor chips. Finally, a downscaled MMC prototype is built; the proposed method is verified by both simulation and experiment.